Skeletal age of individuals with Down syndrome - De Moraes, Mari Eli Leonelli; Tanaka, Jefferson Luis Oshiro; De Moraes, Luis Cesar; Medici Filho, Edmundo; De Melo Castilho, Julio Cezar (Wiley, 2008)
The aim of this study was to assess the skeletal age of Brazilian individuals with Down syndrome (DS) using the method of Greulich and Pyle. Forty subjects with DS between the ages of 6 and 16 years were studied and compared to a control sample of children without DS. The statistical analysis showed that at the age of 7 years the skeletal age (SA) of the individuals with DS was delayed in relation to their chronological age (CA) (SA < CA). On the other hand, at the age of 15 years, their SA was advanced in relation to their CA (SA > CA). An evaluation of the results suggests that the period of adolescent development for individuals with DS was shorter. These individuals reach the completion of bone maturation earlier compared to individuals without DS. © 2008 Special Care Dentistry Association and Wiley Periodicals, Inc.
Keywords: Age determination through skeleton/radiography; Down syndrome; Mental retardation; adolescent; age determination; bone development; Brazil; carpal bone; case control study; child; female; human; male; pathophysiology; radiography; statistical model; Adolescent; Age Determination by Skeleton; Bone Development; Carpal Bones; Case-Control Studies; Child; Down Syndrome; Female; Humans; Linear Models; Male